Peran Kepolisian Dalam Perlindungan Hukum Terhadap Tersangka Anak Selama Proses Penyidikan - Sulis Setyowati (Jurnal Hukum Dan Keadilan, 2010)
Doing an injustice conducted by a child, both for conducted designedly or of necessity, causing his/herself have to experience to with refer to process session of the court of crime since investigation, investigation of child up to prosecution of defendant in court of justice. In course of investigation accompanied with detention to child, even though gone into effect presumption of innocence, just remain to be will bring negative impact related to future the child which still length. Problem of this research is any kind of form protection to child that given by the Police during investigation process and how the implementation of protection to child that given by the Police during investigation process.